Expression of Human NSAID Activated Gene 1 in Mice Leads to Altered Mammary Gland Differentiation and Impaired Lactation. - April K Binder; Justin P Kosak; Kyathanahalli S Janardhan; Glenda Moser; Thomas E Eling; Kenneth S Korach (PLoS ONE)
Transgenic mice expressing human non-steroidal anti-inflammatory drug activated gene 1 (NAG-1) have less adipose tissue, improved insulin sensitivity, lower insulin levels and are resistant to dietary induced obesity. The hNAG-1 expressing mice are more metabolically active with a higher energy expenditure. This study investigates female reproduction in the hNAG-1 transgenic mice and finds the female mice are fertile but have reduced pup survival after birth. Examination of the mammary glands in these mice suggests that hNAG-1 expressing mice have altered mammary epithelial development during pregnancy, including reduced occupancy of the fat pad and increased apoptosis via TUNEL positive cells on lactation day 2. Pups nursing from hNAG-1 expressing dams have reduced milk spots compared to pups nursing from WT dams. When CD-1 pups were cross-fostered with hNAG-1 or WT dams; reduced milk volume was observed in pups nursing from hNAG-1 dams compared to pups nursing from WT dams in a lactation challenge study. Milk was isolated from WT and hNAG-1 dams, and the milk was found to have secreted NAG-1 protein (approximately 25 ng/mL) from hNAG-1 dams. The WT dams had no detectable hNAG-1 in the milk. A decrease in non-esterified free fatty acids in the milk of hNAG-1 dams was observed. Altered milk composition suggests that the pups were receiving inadequate nutrients during perinatal development. To examine this hypothesis serum was isolated from pups and clinical chemistry points were measured. Male and female pups nursing from hNAG-1 dams had reduced serum triglyceride concentrations. Microarray analysis revealed that genes involved in lipid metabolism are differentially expressed in hNAG-1 mammary glands. Furthermore, the expression of Cidea/CIDEA that has been shown to regulate milk lipid secretion in the mammary gland was reduced in hNAG-1 mammary glands. This study suggests that expression of hNAG-1 in mice leads to impaired lactation and reduces pup survival due to altered milk quality and quantity.